The Tribunals' Fact-Finding Legacy - Yvonne McDermott Rees (The Legacy of Ad Hoc Tribunals in International Criminal Law: Assessing the ICTY and the ICTR's Most Significant Legal Accomplishments, 2019)
This chapter draws on the rich and varied jurisprudence of the International Criminal Tribunal for the former Yugoslavia and the International Criminal Tribunal for Rwanda in enunciating some of the key themes that underpinned their fact-finding practices. It provides suggestions on how the standard of proof could be more clearly articulated, how the evaluation of evidence could be made more explicit, and how international criminal judgments could be made more accessible, drawing on the experience of both tribunals. The increased accessibility and clarity that would result would in turn enhance the legal and sociological legitimacy of future international criminal trials.